O KOGNITÍVNEJ SEMIOTIKE. - KLINKENBERG, JEAN-MARIE (Filozofia, 2014)
In the paper, cognitive semiotics is presented as a contemporary semiotic discipline interconnected with humanities as well as - through cognitive sciences - natural sci-ences. The objectives of cognitive semiotics and the above-mentioned sciences can be identical: to shed light on the conditions of the constitution of sense. This consti-tution is conceived of as a modality of cognition and action. Thanks to a possible fruitful dialogue, cognitive semiotics could make use of a new epistemology, which would connect the objective continuum to the discursive one.